Reproducing Do Policymakers Listen to Experts? Evidence from a National Survey of Local and State Policymakers (Lee 2022) - John Hicks; Arianna Bondi; Thomas Gareau-Paquette; Scott Patterson (Institute for Replication (I4R), 2024)
Lee (2022) evaluates whether elected officials update their policy positions based on expert evidence. His cross-subject and within-subject designs run in the American local and state policymaking context both confirm the capacity for politicians to update their beliefs in response to expert evidence, cutting across party-lines and regardless of the valence of the information provided. Our replication finds that the study as published is nearly perfectly replicable following Lee's publicly-available code, with some minor departures that merit revision. Following replication, we offer suggestions for improved clarity of the code, greater transparency with the data accessibility, and clarification of the minor inconsistencies identified between the code and the published work.
Keywords: 330